Percepções dos cidadãos sobre o uso de veículos elétricos leves nos parques urbanos de Campo Grande-MS - KARINE BEZERRA LIMA (2023)
A viable alternative for planning urban mobility in a socially, ecologically and economically sustainable way would be light electric vehicles. This project is a study on the usability of light electric vehicles in parks in Campo Grande - MS. The present work investigates expectations regarding the introduction of electric vehicles in city parks through interviews with potential users of the modal. Due to the analyzes of the Iramuteq Software - analysis of similarity, frequency, multiple frequencies, prototypical - based on the qualified literature on the subject in available public articles and the results of 120 interviews with potential users, it was possible to identify that electric vehicles can be an alternative for sustainable micromobility in cities, as they provide a cleaner, more efficient and sustainable form of transport, contributing to a better quality of life in cities and a more sustainable future for the planet.